2013
DOI: 10.1155/2013/349067
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Progenitor Cells from Childhood Acute Lymphoblastic Leukemia Are Functionally Deficient and Express High Levels of the Transcriptional Repressor Gfi-1

Abstract: Acute lymphoblastic leukemia (ALL) is the most frequent malignancy of childhood. Substantial progress on understanding the cell hierarchy within ALL bone marrow (BM) has been recorded in the last few years, suggesting that both primitive cell fractions and committed lymphoid blasts with immature stem cell-like properties contain leukemia-initiating cells. Nevertheless, the biology of the early progenitors that initiate the lymphoid program remains elusive. The aim of the present study was to investigate the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Remarkably, the cellular communication between leukemic cells and MSC through exosomes or across nanotubes (65, 66) and the disruption of the CXCR4/CXCL12 axis (28, 59), suggesting a key role for G-CSF in this phenomena, are consistent with our previous reports about production of pro-inflammatory factors by tumor cells (30), related to G-CSF and Gfi-1 (29). Accordingly, G-CSF administration in a preclinical model of ALL showed an increased tumor burden (67), and its mechanism may be operating in the niche because B cell malignances rarely expressed G-CSF receptor and are unable to respond in vitro to this cytokine (68).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Remarkably, the cellular communication between leukemic cells and MSC through exosomes or across nanotubes (65, 66) and the disruption of the CXCR4/CXCL12 axis (28, 59), suggesting a key role for G-CSF in this phenomena, are consistent with our previous reports about production of pro-inflammatory factors by tumor cells (30), related to G-CSF and Gfi-1 (29). Accordingly, G-CSF administration in a preclinical model of ALL showed an increased tumor burden (67), and its mechanism may be operating in the niche because B cell malignances rarely expressed G-CSF receptor and are unable to respond in vitro to this cytokine (68).…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, previous work in our lab suggests an important damage in the frequency and function of hematopoietic stem and progenitor cells (HSPC) in the BM of ALL patients accompanied by an abnormal and pro-inflammatory secretion profile (e.g., increased secretion of IL-1β and TNFα) (29, 30). In order to address the molecular pathways involved in hematopoietic and microenvironmental alterations that may favor disease progression, we recently constructed a Boolean model, which demonstrates that constitutive activation of NF-κB in the hematopoietic molecular network was sufficient to establish a positive feedback loop that maintain the constitutive secretion of pro-inflammatory cytokines (e.g., IL-1β and G-CSF) and induce the disruption of the CXCR4/CXCL12 axis, which is crucial for the maintenance of the hematopoietic cells in their regulatory niche.…”
Section: Introductionmentioning
confidence: 95%
“…Concomitant to the massive production of malignant cells, acute leukemias present severe cytopenias and poor reconstitution of the innate and adaptive immune system. We have previously shown that the early compartment of normal stem and progenitor cells within the BM of patients suffering from ALL is critically reduced, both in number and functional activity …”
Section: Resultsmentioning
confidence: 99%
“…2,3 The disease is characterized by uncontrolled oligoclonal proliferation of lymphoid precursors, mostly B lineage, within the bone marrow (BM), with relapses occurring in approximately 20-30% of cases due to minimal residual disease and a failure in the mechanisms of cell-mediated antitumor immune surveillance. [4][5][6] Among other crucial functions, the immune system prevents tumor emergence through identification and elimination of incipient malignant growths, at three functional levels: by protecting the host from oncogenic viral infections, by solving inflammatory processes thus preventing oncopromotion by inflammatory microenvironments, and by direct elimination of tumor cells upon immune cell recognition. 7 NK cells are responsible for early responses mediated by release of cytokines capable of lysing tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…ALL leukemia progenitors are known to be functionally deficient in their lymphoid and myeloid differentiation potentials, and this behavior may result from both, intrinsic and extrinsic abnormalities within the ALL hematopoietic system [8] . Moreover, ALL relapse often display lineage switching or mixed phenotypes, though the involved mechanisms are still poorly understood [9] .…”
Section: Research Highlightmentioning
confidence: 99%